Endovascular management of a spontaneous aorto-caval fistula resulting from abdominal aortic aneurysm: case report and literature review - Dongbo Wu; Cheng Peng; Zhiyong Zhou; Jie Chen; Bin He; Zhidong Ye (Frontiers in Cardiovascular Medicine)
BackgroundAorto-caval fistula is a rare complication of abdominal aortic aneurysms that can occur spontaneously, iatrogenically, or traumatically, associated with high morbidity and mortality. Endovascular stent graft repair represents a practical approach to managing this fatal condition.Case presentationA 75-year-old male patient was admitted to the nephrology department of our hospital, complaining of acute back pain, hematuria, and repeated vomiting for one week. The laboratory assessments yielded high creatinine levels, indicating an acute renal impairment. Computed tomography angiography revealed an aorto-caval fistula complicating infrarenal abdominal aortic aneurysm. The patient was successfully treated with the endovascular approach by deploying covered stent grafts that completely excluded the fistula.ConclusionUtilizing covered stent grafts for endovascular management of aorto-caval fistula is a good alternative to conventional surgery, especially in elderly high-risk patients.